Clinicopathological Characteristics Related to Etiologies of Erythema Nodosum: A 10-Year Retrospective Study - Limtong P; Suchonwanit P; Chanprapaph K; Rutnin S (Dove Medical Press, 2021)
Preeyachat Limtong, Poonkiat Suchonwanit, Kumutnart Chanprapaph, Suthinee Rutnin Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Suthinee RutninDivision of Dermatology, Department of Internal Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, ThailandTel +66 2-2011141Fax +66 2-201-1211 ext 4Email suthinee.rutnin@gmail.comBackground: Erythema nodosum (EN) is the most common panniculitis associated with a wide variety of conditions. Updated studies regarding the clinicopathological manifestations related to etiologies of EN and its prognosis are limited.Objective: We aimed to explore the clinicopathological features in relation to the etiologies of EN and determine characteristics of disease recurrence and its predictive factors.Methods: A total of 169 patients with biopsy-proven EN or septal panniculitis from January 2008 to September 2018 were retrospectively reviewed. Patients were classified as either idiopathic or secondary EN. Patients' general information, clinical manifestations, investigations, and recurrence of EN were recorded. The details on histopathological findings were reviewed by a blinded dermatopathologist.Results: The mean age at diagnosis of EN was 40.6 ± 17.3 years. The majority of patients (85.2%) were female. Idiopathic EN was found in 62.7% of patients. Tuberculosis (23.8%) and drugs (23.8%) were the leading causes of secondary EN. In univariate logistic regression analysis, lesions on upper extremities (p = 0.018), fever (p = 0.003), clinical lymphadenopathy (p < 0.001) favored secondary EN. Histopathologically, the presence of focal peripheral lobular panniculitis with eosinophils was linked to idiopathic EN (p = 0.03). However, multivariable logistic regression analysis failed to demonstrate factors associated with secondary EN. Recurrence was found in 46.6% of patients with no identifiable predictive factors.Conclusion: Although no clinical risk factors were associated with the etiology of EN, the histopathological presence of eosinophils in focal peripheral lobular panniculitis suggested idiopathic EN.Keywords: leg nodules, panniculitis, septal panniculitis, subcutaneous nodule, subcutaneous mass